Damage tolerance of adhesively bonded pultruded GFRP double-strap joints - Fame,CM; Correia,JR; Ghafoori,E; Wu,C (Composite Structures, 2021)
Compared with mechanical fastening, adhesive bonding offers numerous advantages in the joining of pultruded glass fiber reinforced polymer (GFRP) sections. However, one critical issue associated with bonded joints is the assessment of their mechanical behavior considering bondline defects. This paper presents the results of an experimental investigation of the damage tolerance of adhesively bonded pultruded GFRP joints considering bondline defects. Double-strap specimens with and without bondline defects were prepared and tested in tension until failure. The location (five different locations in the bond length and width directions), size (10%, 20%, and 30% of the total bonded area in both the bond length and width directions), shape (triangular, rectangular, square, circular, and elliptical), and number (between 1 and 8) of defects within the bondline were considered as variable parameters. This paper reports and discusses the observed failure modes, load–displacement curves, and joint capacities, considering the effects of bondline defects. Interface debonding was observed in regions neighboring the bondline defects, and delamination was observed in other bonded areas. All joints exhibited a linear elastic load–displacement response with sudden and brittle failure, regardless of the presence of bondline defects. The observed capacity reduction of up to 33% could be significant if the defects were located at the edges of the bonded area. Defects of different shapes resulted in similar reductions in joint capacity (21%). Furthermore, the joint was found to be more sensitive to irregularly shaped (e.g., triangular) defects, and reducing the number of defects was more effective in mitigating the reduction in joint capacity than reducing the total defect area was.